Collaborative Intelligence: Integrating Artificial Intelligence with Emotional Intelligence for Enhanced Customer Experience - bhandari, Geetanjali; bhandari, Geetanjali; Jain, Ruchi (International Journal of Psychosocial Rehabilitation, 2020)
This paper explores the prospect of amalgamating artificial intelligence with emotional intelligence for attaining higher customer satisfaction. The paper delves to fathom how technology can overture personalization in selling process and thus create enhanced customer experience. The paper highlights various touch points in a retail setting in conjugation with the complementary benefits sales force can harness by the aiding technology of artificial intelligence. It throws light on the paradigm shift brick and mortar stores are experiencing with the advent of digitalization. It blankets the change of a retail store blueprint to a digitized blueprint along with the change of retail servicescape to a digital servicescape. Resultantly, the paper proposes a conceptual framework featuring Collaborative Intelligence through delight maximization in customers with respect to their interaction with retail sales associate, as a result of integrating effect created by emotional intelligence and artificial intelligence. It is a unique paper pioneering in showcasing various technologies that can be used by retailers for intensifying customer engagement and for creating memorable experiences for greater customer satisfaction, delight and positively impact the bottom line.